Estimação da temperatura de corte utilizando problemas inversos em condução de calor - Melo, Anderson Clayton Alves de (1998)
A method to estimate the chip-tool interface temperature on octahedron inserts, using inverse problems techniques in heat conduction is proposed. A sequencial algorithm to determine the heat flow at the interface is used. An ellipsoidal model is used in order to consider the isotherms generated during the process of tool heating as a family of ellipsoids having the same focus. The heat conduction involved in the machining process is numerically considered based on finite diferences. In order to validate the proposed method , Si3N4 based ceramic and cemented Carbide (K10) inserts were used for turning grey cast iron (NB-FC200). During machining a T type thermocouple mounted at the opposite bottom edge, between the insert face and the tool holder, monitored the temperature in real time. The results presented estimated values pretty close to the measured ones and similar to those encountered in the literature, particularly when using cemented Carbide tools. The method showed a great sensibility to changes of some geometric parameters such as chip-tool contact area and position of the thermocouple. Diffícultion in precisely determine these parameters may justify possible errors of estimation.